Dieulafoy lesion presenting as severe anaemia in a soldier. Issue 1 (29th May 2013) - Burley, Robert MW; Gavrielides, I
Abstract : An unusual presentation of severe anaemia in a young soldier is presented. A brief review of the nature of Dieulafoy lesions and treatment and difficulties of managing these in military primary care is considered.